2016
DOI: 10.1016/j.bbrc.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6 and 7 are biomarkers for fatigue, which distinguish between physiological fatigue and pathological fatigue

Abstract: Fatigue reduces productivity and is a risk factor for lifestyle diseases and mental disorders. Everyone experiences physiological fatigue and recovers with rest. Pathological fatigue, however, greatly reduces quality of life and requires therapeutic interventions. It is therefore necessary to distinguish between the two but there has been no biomarker for this. We report on the measurement of salivary human herpesvirus (HHV-) 6 and HHV-7 as biomarkers for quantifying physiological fatigue. They increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
6
28
0
3
Order By: Relevance
“…No difference between severity of symptoms and viral load of HHV-6 and HHV-7 in saliva and PBMC of ME/CFS patients and controls was shown [ 69 ]. Besides, detectable reactivation of HHV-6A/6B and HHV-7 in saliva is considered as a biomarker for physiological fatigue, and can therefore be used to distinguish between pathological and physiological fatigue [ 70 ].…”
Section: Human Herpesvirusesmentioning
confidence: 99%
“…No difference between severity of symptoms and viral load of HHV-6 and HHV-7 in saliva and PBMC of ME/CFS patients and controls was shown [ 69 ]. Besides, detectable reactivation of HHV-6A/6B and HHV-7 in saliva is considered as a biomarker for physiological fatigue, and can therefore be used to distinguish between pathological and physiological fatigue [ 70 ].…”
Section: Human Herpesvirusesmentioning
confidence: 99%
“…In addition, we previously demonstrated that salivary HHV‐6 DNA levels were elevated by factors such as increased caregiver burden and strenuous military training . Although the influence of stressors like these on the results of the present study cannot be ruled out, its subjects were, at the minimum, people working in the same company not doing physical work.…”
Section: Discussionmentioning
confidence: 69%
“…дженні продемонстрували нещодавно, що саме ідентифікація HHV-6 і HHV-7 може бути критерієм розрізнення фізіологічної і патологічної слабкості у людей [9]. Як стало відомо нині, розвиваючи хронічну реактивовану інфекцію у пацієнтів з передіснуючою імунною дисфункцією, герпесвіруси здатні індукувати стійку системну імунозапальну відповідь, яка призводить до генерації відчуття вираженої слабкості завдяки впливу прозапальних цитокінів на нейрони медіанних відділів скроневих часток великого мозку.…”
Section: огляд /Review/ рисунок 2 посилення гуморальної відповіді доunclassified